2019
DOI: 10.1101/815654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heritability and family-based GWAS analyses of the N-acyl ethanolamine and ceramide plasma lipidome

Abstract: Certain signalling lipids of the N-acyl ethanolamine (NAE) and ceramide (CER) classes are emerging as novel biomarkers of cardiovascular disease. We sought to establish the heritability of plasma NAEs (including endocannabinoid anandamide) and CERs, and identify common DNA variants influencing the circulating concentrations of the heritable lipid species. Eleven NAEs and thirty CERs were analysed in plasma samples from 999 members of 196 British Caucasian families, using targeted mass spectrometry-based lipido… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…By contrast, our study found high heritability of ceramides, and no significantly heritable SMs and virtually zero heritability of LPCs. A more recent publication of a Finnish population based study (FINRISK) reported SNP-based heritability of lipid species to be in the range 0.10–0.54 ( Tabassum et al, 2019 ), and found Cer to be the most heritable species, corroborating findings from the present study and others ( McGurk et al, 2017 ; McGurk et al, 2019 ), though heritability of some other lipid classes, such as LPC was markedly higher than reported in the present study. We have summarised our findings against the backdrop of previous literature in Table 5 .…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, our study found high heritability of ceramides, and no significantly heritable SMs and virtually zero heritability of LPCs. A more recent publication of a Finnish population based study (FINRISK) reported SNP-based heritability of lipid species to be in the range 0.10–0.54 ( Tabassum et al, 2019 ), and found Cer to be the most heritable species, corroborating findings from the present study and others ( McGurk et al, 2017 ; McGurk et al, 2019 ), though heritability of some other lipid classes, such as LPC was markedly higher than reported in the present study. We have summarised our findings against the backdrop of previous literature in Table 5 .…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, TwinsUK reported varied estimates for steroids and BAs [1]. McGurk et al [22] reported heritability estimates ranging 45-82% for 11 plasma N-acylethanolamide (NAE) analytes in 196 families. In this study lower heritability estimates are reported for 7 NAEs (AEA, PEA, OEA, DHEA, SEA, LEA, POEA), possibly due to different biofluids and modelling methodology.…”
Section: Discussionmentioning
confidence: 99%
“…Extraction and analysis of endocannabinoids, NAE, 2-monoacylglycerols (MAG), ceramides, phosphorylated ceramides, free and phosphorylated sphingoid bases were performed as described previously. 21,45,46 Briefly, plasma (1 ml) was spiked with a mixture of deuterated internal standards (20 ng of AEA-d8, 40 ng of 2-AG-d8 and 50 pmol of Cer/Sph Mixture I; Cayman Chemicals, Ann Arbour, MI, USA; Avanti Polar Lipids, USA) and lipids were extracted with ice-cold chloroform:methanol (2:1, v/v). Lipid extracts were analyzed by UPLC-MS/MS using a C18 column (50 × 2.1 mm, 1.7 μm; Acquity UPLC BEH; Waters) for NAE and 2-MAG, and a C8 column (100 × 2.1 mm, 1.7 μm; Acquity UPLC BEH; Waters) for ceramides.…”
Section: Methodsmentioning
confidence: 99%